Dance therapy as a method of rehabilitation in rheumatic diseases - E. V. Matyanova; E. Yu. Polishchuk; O. V. Kondrasheva; A. E. Karateev; A. M. Lila (Современная ревматология, 2023)
A dance is considered from the perspective of art therapy, psychotherapy and kinesiotherapy as a component of therapeutic exercises. Previous experience with dance therapy in various rheumatic diseases is presented, and a theoretical rationale for adapting new dance styles for the purposes of complex non-drug treatment of rheumatologic patients is provided.